2004
DOI: 10.1097/00005131-200411000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Complications Associated With Internal Fixation of High-Energy Bicondylar Tibial Plateau Fractures Utilizing a Two-Incision Technique

Abstract: Comminuted bicondylar tibial plateau fractures can be successfully treated with open reduction and medial and lateral plate fixation using 2 incisions. Dysvascular limbs requiring vascular repair are at increased risk for deep sepsis. The use of 2 incisions, temporary spanning external fixation, and proper soft-tissue handling may contribute to a lower wound complication rate than previously reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
289
3
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(313 citation statements)
references
References 29 publications
11
289
3
10
Order By: Relevance
“…Harborview reported 14.5% compartment syndrome in a similar population [2]. Our study showed a 10% rate of compartment syndrome treated with fasciotomies, very much in line with the existing literature, and the timing of the application of the external fixator did not correlate with the diagnosis of compartment syndrome.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Harborview reported 14.5% compartment syndrome in a similar population [2]. Our study showed a 10% rate of compartment syndrome treated with fasciotomies, very much in line with the existing literature, and the timing of the application of the external fixator did not correlate with the diagnosis of compartment syndrome.…”
Section: Discussionsupporting
confidence: 89%
“…Multiple studies have demonstrated reduced infection rates with this protocol [2,[4][5][6]12]. However, the question of the urgency with which the temporizing external fixation must be applied has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial cultures were grown in Cation Adjusted Mueller Hinton Broth to an optical density (OD) 600 1.259 g of D-Met, and 1.259 g of D-Phe in 100 mL culture medium (aMEM; Sigma) supplemented with 10% fetal bovine serum, 100 IU/mL penicillin, and 100 lg/mL streptomycin) at 37 o C and adjusting to pH 7.5 to 8 using 0.5 N HCl. D-AA stock solution was diluted with culture medium to achieve the targeted concentration, and culture medium and D-AAs were refreshed every other day.…”
Section: Biofilm Inhibition and Dispersal Assaysmentioning
confidence: 99%
“…Although clinical studies have underscored the relationship between infection and nonunion of diaphyseal fractures [24], periarticular fractures also have high rates of infections complications. The deep infection rate of patients with Schatzker Type VI bicondylar tibial plateau fractures treated by a two-incision dual-plating technique ranged from 11% to 23% [1,43] and approached 30% if treated more than 72 hours after injury [19]. Thus, inhibiting the formation of a biofilm may be an alternative strategy for reducing the incidence of infectious complications and nonunions.…”
Section: Introductionmentioning
confidence: 99%